Strains in Asphalt Pavements Under Circular and Rectangular Footprints - Massimo Losa; Andrea Di Natale (The Baltic Journal of Road and Bridge Engineering)
The analysis of flexible pavements is usually carried out by the Linear Elastic Theory in axial-symmetric configuration, and by assuming that stresses are uniformly distributed over a circular footprint. The application of these methods requires simple computations, but beside this, the approximation of the real geometry with circular footprints causes erroneous results in the stress-strain response and therefore in the damage analysis. Rectangular footprint is closer to the real shape of the tire/pavement contact area. This paper aims to identify some relations to evaluate the effective strains induced in pavements by rectangular footprint loads by considering an equivalent single or group of circular footprints. In order to achieve this goal, pavement response was evaluated for different variable combinations both by ViscoRoute 2.0 software for the rectangular footprint, and by an elastic model for the circular footprint in axial-symmetric configuration; results obtained by the two analyses were compared in order to develop two different models. The first model proposes a correction coefficient λ of the radius of the circular area to be used for calculating strains beneath the centre of the rectangular footprint. The correction coefficient λ calculated for different variable configurations were related to those variables regarded as significant by means of a multivariate regression. In the second model, in order to calculate strains outside the rectangular footprint, the superposition of circular footprints that better approximates the rectangular ones was determined.